SISTEM MONITORING LEVEL AIR RADIATOR KENDARAAN DENGAN METODE FUZZY - Dina Hervita; Ahmad Taqwa; Martinus Mujur Rose (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2017)
Almost every vehicle will need maintenance such as oil change, tire change, water radiator, brake, engine parts and much more. However, sometimes vehicle owners are less concerned with the condition of the vehicle and often ignore the treatment. This can be bad, it can even lead to an accident. Therefore, the monitoring system is designed to monitor the level of radiator water in vehicle tanks. The ultrasonic sensor will measure the water level of the radiator in the r eservoir tank. If the water level of the radiator in the tank is low then the pump will automatically recharge the radiator water and the buzzer will sound faster. The data from the ultrasonic sensor will be sent to the microcontroller with fuzzy logic. Ve hicle owners can access information in the form of water level radiator in the tank via wifi module and wifi router. So the problem of damage to the vehicle can be overcome quickly, easily, and efficiently.